Internal Sources to Increase Financing for Fixed Investments in a Company - Oleg Mikhaylovich Turygin (Экономика региона, 2018)
Increasing fixed investments is the main task for the Russian economy. The restriction on the ability of a company to attract external financing demands increasing investments from the company’s own funds. The purpose of the research is to identify reserves for the increase in fixed investments from internal funds. Using data on the economy, in general, I have found that the most part of net profit is used for dividend payments (54 %) and financial investments (38 %) and only 8 % of a company’s net profit is invested into fixed capital. It proves that the financial policy of the Russian companies is focused on a short-term income to the detriment of long-term returns. I have proposed a methodology, which allows to define the company’s reserves for the increase in fixed investments from its own funds depending on an economically reasonable target value for the share of net operating surplus, which is directed to fixed investments. When the target level of net fixed investment is 50 % of net operating surplus, the fixed investments from the company’s own funds can be increased by 1.53 times or by 2.84 trillion rubles that makes 3.3 % of GDP for the total economy. The maximum opportunities for the increase in fixed investments at the expense of own means are available in the oil production (by 1.83 times), metallurgical production (by 1.76 times) as well as wholesale trade of fuel (by 34.6 times). State policy has to stimulate the companies to the greatest possible use of their own funds to invest into fixed capital. The results of the research can be used to select the companies applying for state support.